2016
DOI: 10.1007/s12119-016-9389-3
|View full text |Cite
|
Sign up to set email alerts
|

Gay Men’s Construction and Management of Identity on Grindr

Abstract: This study explores gay men's construction and management of identity on Grindr. A sample of gay men was interviewed and the data were analyzed using Interpretative Phenomenological Analysis. The following themes are outlined: (1) Constructing and re-constructing identities on Grindr; (2) Bolstering sexual self-efficacy; (3) Managing online and offline identities. Despite the apparent social psychological benefits of geospational gay social networking applications, the pressures of coercive norms on the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Furthermore, research has shown that gay mobile applications are perceived to constitute a 'safer' sex for avoiding involuntary disclosure of one's sexual orientation, which itself may be associated with homophobia. 27 There were significant differences in engagement in sexual risk-taking behaviours by ethnicity and HIV status. Latino respondents are more likely to frequent gay saunas and to report drug use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research has shown that gay mobile applications are perceived to constitute a 'safer' sex for avoiding involuntary disclosure of one's sexual orientation, which itself may be associated with homophobia. 27 There were significant differences in engagement in sexual risk-taking behaviours by ethnicity and HIV status. Latino respondents are more likely to frequent gay saunas and to report drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences of prejudice may also affect the ways in which BME MSM seek sexual encounters with other men; indeed, there was a positive relationship between frequency of racism and sex seeking on mobile applications across all ethnic groups. It has been found that some MSM may perceive greater confidence and self-efficacy in relation to sex seeking and interactions with other men than in offline settings, 27 which may explain the preference for this forum among BME MSM who have experienced racism (including from other MSM). Furthermore, research has shown that gay mobile applications are perceived to constitute a 'safer' sex for avoiding involuntary disclosure of one's sexual orientation, which itself may be associated with homophobia.…”
Section: Discussionmentioning
confidence: 99%
“…My work differs from some recent investigations on hook-up apps which have a strong focus on identity/psychological features and the ways users describe themselves or their strategies of self-presentation (Miller, 2015). Like Jaspal (2016), I also share the view that focusing investigations on the conscious management of identity in the use of hook-up apps is not enough to explain the complex dynamics between vision and desire found therein. I am working within a deconstructionist perspective that puts those aspects in a more complex web of relations that involve not only conscious but also unconscious aspects of desire in the production of identity.…”
Section: Introductionmentioning
confidence: 77%
“…This shift in attention becomes clearer when comparing previous research on Grindr with this article's analysis. If I were to unpack Grindr's homonormativity, I might note how users' profiles frame good gay bodies as sporty and muscular (Enguix & Gómez-Narváez, 2018;Miller, 2018) and produce racist, hegemonically masculine affects (Jaspal, 2017;Penney, 2014). In contrast, I am concerned with how Grindr enacts power not through messages about queerness but by constituting a complex, extractive queer space in the first place.…”
Section: Reading (For Capitalism) Is Fundamental: From Homonormativitmentioning
confidence: 99%